2018
DOI: 10.1007/s11845-018-1886-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and co-variates of burnout in consultant hospital doctors: burnout in consultants in Ireland Study (BICDIS)

Abstract: This study demonstrated that over 40% of the consultants studied are affected by burnout. This finding raises concerns for patient safety and standard of care as well as doctors well-being. Interventions to address and minimise burnout are important to guarantee high patient outcomes and retain medical staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…This is the first study examining levels of BO among consultant child and adolescent psychiatrists in Ireland, set against a background of unprecedented consultant vacancies and increasing CAMHS referrals. Although the response rate (46%) was lower than hoped, it is comparable to that found in studies among consultants in Ireland (42%–55%),9 22 studies within psychiatry (26%)27 and studies using CBI (22.5%–40%) 20 21. It is unclear whether non-response would preferentially apply to busy overworked clinicians with high BO levels, too exhausted to participate, or if respondents are more likely to reflect those who had indeed experienced BO and wanted to have their voice heard.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…This is the first study examining levels of BO among consultant child and adolescent psychiatrists in Ireland, set against a background of unprecedented consultant vacancies and increasing CAMHS referrals. Although the response rate (46%) was lower than hoped, it is comparable to that found in studies among consultants in Ireland (42%–55%),9 22 studies within psychiatry (26%)27 and studies using CBI (22.5%–40%) 20 21. It is unclear whether non-response would preferentially apply to busy overworked clinicians with high BO levels, too exhausted to participate, or if respondents are more likely to reflect those who had indeed experienced BO and wanted to have their voice heard.…”
Section: Discussionmentioning
confidence: 70%
“…In a sample of 1037 Australian midwives, equivalent prevalence rates were also much lower (43.8% for work-related BO and 64.9% for personal) than that found among child psychiatry consultants practicing in Ireland 21. Two other studies examining doctors working in Irish hospitals reported rates of BO considered by the authors to be higher than their European colleagues, with junior doctors being most at risk 9 22…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In the UK, the improving access to psychological therapies (IAPT) initiative has introduced over 6,000 newly trained low‐ and high‐intensity therapists to the National Health Service (NHS) since it was launched in 2008 (National Health Service, 2015). The work of psychological therapists involves a high degree of face‐to‐face client work, which is known to increase risk of burnout (Margiotta, Crudden, Byrne, & Doherty, 2018), and one study reported that 69% of IAPT therapists met criteria for burnout (Westwood, Morison, Allt, & Holmes, 2017).…”
Section: Introductionmentioning
confidence: 99%